Business Ethics: Concepts and Cases - Manuel G. Velasquez (Harlow, England Pearson, 2014)
Resolving Moral Issues in Business. The ethical landscape of business is constantly changing, and the new edition of Business Ethics: Concepts and Cases has been revised to keep pace with those changes most effecting business: accelerating globalization, constant technological updates, proliferating of business scandals. Business Ethics: Concepts and Cases introduces the reader to the ethical concepts that are relevant to resolving moral issues in business; imparts the reasoning and analytical skills needed to apply ethical concepts to business decisions; identifies moral issues specific to a business; provides an understanding of the social, technological, and natural environments within which moral issues in business arise; and supplies case studies of actual moral conflicts faced by businesses.
Keywords: Business; Textbooks; Management; Philosophy; History; Business ethics; Global Citizenship (BIN1064-N)